2020
DOI: 10.1108/bjm-03-2020-0091
|View full text |Cite
|
Sign up to set email alerts
|

Market-oriented CSR implementation in SMEs with sustainable innovations: an action research approach

Abstract: PurposeThe purpose of the study is to identify and analyze critical mediating and moderating market intelligence challenges faced by the SMEs when implementing corporate social responsibility (CSR) based on an applied market-oriented business model (MOBM).Design/methodology/approachFocusing on developing CSR-integrated market intelligence, this study uses an action research method by analyzing four case studies. Data is collected through interviews, interactive and knowledge-sharing meetings and on-site observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Given that several recent research papers address CSR's role in enhancing sustainable business (e.g., Samy et al., 2010 ; Sundström et al., 2020 ), the business environment's complexity and business capacity are inspiring more in-depth multi-dimensional studies. With the intention of expanding the literature of CSR, especially in the context of Vietnam, this study contributes empirical evidence by testing the mediating model of ethical leadership, CSR, firm reputation and firm performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that several recent research papers address CSR's role in enhancing sustainable business (e.g., Samy et al., 2010 ; Sundström et al., 2020 ), the business environment's complexity and business capacity are inspiring more in-depth multi-dimensional studies. With the intention of expanding the literature of CSR, especially in the context of Vietnam, this study contributes empirical evidence by testing the mediating model of ethical leadership, CSR, firm reputation and firm performance.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that CSR activities' firm reputation positively affects firm performance in both financial and non-financial terms. By correctly implementing CSR, firms can convert their reputation into increased profit, talent and customers to establish a sustainable competitive advantage ( Black et al., 2000 ; Sabate and Puente, 2003 ; Sundström et al., 2020 ). Finally, the analysis showed a correlation between CSR and firm performance.…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects of the innovations management as a business process during building the SDGs in the corporate strategies are reflected in several works (Bolz and de Bruin 2019;Golini and Gualandris 2018;Kneipp et al 2019;Martínez-Mora and Merino 2020;Ogoh and Fairweather 2019;Severo et al 2020;Sundström et al 2020;Yaghmaei 2018).…”
Section: Innovative Activities Management In Entrepreneurship In the Interests Of Sustainable Developmentmentioning
confidence: 99%
“…Business models assist SMEs in taking initiative to anticipate, address, and push for efficient changes in market approach (Skarzynski & Rufat-Latre, 2011). Sundström et al (2020) suggest that network-based business models contribute to the otherwise unaquirable exchange of experience between different stakeholders. Our study investigated how SMEs can develop network-based MO knowledge for the internationalization of DI.…”
Section: Introductionmentioning
confidence: 99%